40 Years of Boris Pasternak Research in China - Shubi Ren; Yong Wang (Научный диалог, 2024)
The creative path of B. L. Pasternak has been a popular subject of research in China for many years. All works on the topic can be roughly divided into three stages: 1) the first stage (1980s) — the formation of mass interest among literary scholars in the works of B. L. Pasternak; 2) the second stage (1990s) — the expansion and deepening of research; 3) the third stage (after the 2000s) – the systematization of research and the emergence of new directions in the study of B. L. Pasternak’s works. This article provides an overview of the main trends in Pasternak studies in China. It is noted that research on the legacy of B. L. Pasternak conducted in China covers key areas such as biography, poetry, prose (with special attention from Chinese scholars focused on the novel “Doctor Zhivago”). The research conducted by Chinese scholars also explores topics such as the fate of the intelligentsia, ideological aspirations, cultural, religious, and spiritual components, the art of language, literary techniques, and devices. It is reported that in November 2020, Zhejiang University held an international scientific conference “Celebrating the 130th Anniversary of B. L. Pasternak’s Birth.” The authors of the article conclude that research on the legacy of B. L. Pasternak in China is systematic and diverse, and Pasternak studies as a discipline have broad prospects for development.